2012
DOI: 10.1186/1471-2350-13-61
|View full text |Cite
|
Sign up to set email alerts
|

Association of ALOX5APgene single nucleotide polymorphisms and cerebral infarction in the Han population of northern China

Abstract: BackgroundTo explore the association of ALOX5AP single nucleotide polymorphisms (SNPs) and haplotype with the occurrence of cerebral infarction in the Han population of northern China.MethodsBlood samples were collected from 236 patients of Han ancestry with a history of cerebral infarction and 219 healthy subjects of Han ancestry with no history of cerebral infarction or cardiovascular disease. Applied Biosystems® TaqMan® SNP Genotyping Assays for SNP genotyping were used to determine the genotypes of 7 ALOX5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…The risk of CI may vary according to the presence of various genetic and environmental factors. In addition, the relationship between the functional variation of multiple gene in different ethnic groups and CI risk has been studied, including the polymorphisms of interleukin-6 gene [ 2 ], β-fibrinogen gene [ 3 ], PON1 hypermethylation and PON3 hypomethylation [ 4 ], 5-lipoxygenase-activating protein gene association (ALOX5AP) [ 5 ], the cytochrome P450 1A1 (CYP1A1) gene [ 6 ], the human scavenger receptor class B type I (SR-BI) gene [ 7 ], genes associated with lipid metabolism [ 8 , 9 ], and others [ 10 ]. In general, it is important for both risk prediction and prevention of CI by identifying genetic risk.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of CI may vary according to the presence of various genetic and environmental factors. In addition, the relationship between the functional variation of multiple gene in different ethnic groups and CI risk has been studied, including the polymorphisms of interleukin-6 gene [ 2 ], β-fibrinogen gene [ 3 ], PON1 hypermethylation and PON3 hypomethylation [ 4 ], 5-lipoxygenase-activating protein gene association (ALOX5AP) [ 5 ], the cytochrome P450 1A1 (CYP1A1) gene [ 6 ], the human scavenger receptor class B type I (SR-BI) gene [ 7 ], genes associated with lipid metabolism [ 8 , 9 ], and others [ 10 ]. In general, it is important for both risk prediction and prevention of CI by identifying genetic risk.…”
Section: Introductionmentioning
confidence: 99%
“…Another study carried out in a large Chinese cohort reported a significant association of SG13S114AA genotype with a 1.62 fold risk for thrombotic stroke. The other variants of ALOX5AP gene evaluated in the study did not associate with stroke or its subtypes [21]. Kaushal et al (2007) found rs957640 and rs769874 to be associated with stroke in Whites in the United State (US) [22].…”
Section: Discussionmentioning
confidence: 96%
“…Unlike the results of other existing studies on myocardial infarction area [5,7], the results achieved by the authors revealed that the total number of differentially expressed lncRNAs in the border zone was more than that of the myocardial infarction area, demonstrating more occurrences of active and more complex biological processes. For instance, LncRNA: AY212271, showing a coexpression relationship to Alox5ap, might be involved in various in ammatory reactions [12][13][14][15][16]. EF424788 and MRAK088538 were co-expressed with Itgb2, and Itgb2 was reported to be a risk factor for myocardial infarction and atherosclerotic thrombotic cerebral infarction [17][18][19].…”
Section: Discussionmentioning
confidence: 99%